Algoritma Moral: Rekonstruksi Agency Etis Peserta Didik Dalam Pendidikan Agama Islam Di Era Kecerdasan Buatan - Shalih, Badrus; Marzuqi Marzuqi; Abidin , Zainal (PT. Banjarese Pacific Indonesia, 2026)
The rapid advancement of artificial intelligence (AI) carries profound implications for the moral and ethical order of students, particularly within the context of Islamic Religious Education (PAI). This study aims to analyze AI’s disruption of students’ moral development, conduct an epistemological critique of existing PAI approaches, and formulate a model for reconstructing ethical agency based on Islamic values. Using a conceptual qualitative approach through library research, this study integrates perspectives from Islamic moral philosophy, contemporary moral agency theory, and critical analysis of digital education literature. The findings reveal that AI has created a condition of “algorithmic moral passivity,” in which students tend to delegate ethical deliberation to automated systems, resulting in the erosion of moral ijtihad capacity. Grounded in Islamic concepts of ‘aql, nafs, and ikhtiyar, this research proposes a Model of Ethical Agency Reconstruction (MRAE) comprising three dimensions: digital tazkiyatun nafs, technology fiqh, and algorithmic musyawarah. This model is intended to serve as an operational framework for PAI teachers in responding to AI-era challenges in a transformative and contextual manner.